A myostatin inhibitory antibody combined with insulin, partially rescues the musculoskeletal phenotype of female insulin-deficient diabetic mice - R. Clay Bunn; Reuben Adatorwovor; Philip D. Ray; Alexander R. Keeble; Christopher S. Fry; Sasidhar Uppuganti; Jeffry S. Nyman; John L. Fowlkes; Evangelia Kalaitzoglou (Frontiers in Endocrinology)
IntroductionType 1 diabetes is associated with deficits in both skeletal muscle and bone. Inhibition of myostatin, a negative regulator of muscle mass, was explored as a druggable target to improve the musculoskeletal phenotype associated with insulin-deficient diabetes in female mice.MethodsWe investigated whether administration of an inhibitory myostatin antibody (MyoAb) in streptozotocin-induced diabetes in female mice is protective for skeletal muscle and bone. DBA/2J female mice were injected with low-dose streptozotocin or with citrate buffer (vehicle). Subsequently, mice were implanted with insulin-containing or vehicle pellets, with groups being randomized to myostatin or control antibody for 8 weeks. At study end, body composition and in vivo contractile muscle function were assessed, systemic myostatin and glycated hemoglobin were quantified, gastrocnemii were weighed and analyzed for fiber type composition, and femur microarchitecture and biomechanical properties were analyzed.ResultsGlycated hemoglobin was significantly higher in diabetic mice compared to non-diabetic mice and diabetic mice treated with insulin. In diabetic mice, the combination of insulin and MyoAb resulted in higher lean mass, higher average gastrocnemius weight and larger muscle fiber size (Type IIB, IIX and hybrid fibers) compared to no treatment. In vivo contractile muscle function testing showed that insulin increased muscle torque in diabetic mice, however there was no effect of the MyoAb. Lastly, microarchitecture analysis of the distal femur showed improvement in some, but not all trabecular bone properties, in mice treated with insulin alone or together with MyoAb. Specifically, trabecular thickness and trabecular bone volume fraction were higher with combination treatment compared to insulin treatment alone.ConclusionsMyostatin inhibition when used in conjunction with insulin treatment improves muscle mass and trabecular bone properties in a mouse model of insulin-deficient diabetes in female mice.